Effect of local inoculum on the spread of sweetpotato virus disease: limited infection of susceptible cultivars following widespread cultivation of a resistant sweetpotato cultivar - Aritua, Valentine; Legg, James P.; Smit, N.E.; Gibson, R.W. (Wiley, 1999)
A study compared the spread of sweet potato virus disease (SPVD) into crops of two moderately resistant and initially SPVD-free sweet potato cultivars in northern and southern Mpigi, Uganda. Whiteflies, the vector of sweet potato chlorotic stunt crini virus (SPCSV), a component cause of SPVD, were similarly abundant in farmers' sweet potato fields around Namulonge in northern Mpigi, and Kanoni in southern Mpigi. However, mean incidence of SPVD in farmers' crops neighbouring the trials was higher at Kanoni (13·3%) than at Namulonge (2·8%). Furthermore, spread of SPVD into initially SPVD-free sweet potato plots of two only moderately resistant cultivars was greater in plots at Kanoni than in plots at Namulonge. The SPVD-resistant New Kawogo was the most common cultivar grown in farmers' fields at Namulonge and had few diseased plants, whereas susceptible cultivars with relatively high incidences of disease predominated at Kanoni. Final SPVD incidence in each trial was positively correlated with a measure combining the proximity and level of inoculum in surrounding fields. The study demonstrates the importance of local SPVD inoculum in determining the rate of spread of the disease into fields and implies that the widespread cultivation of a resistant variety limits infection of susceptible cultivars grown nearby